About methods of combinatorial optimization, that are based on recognition of input data, heuristic algoritms and calculable intellect - Tymofiieva, N. K. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The methods of combinatory optimization based on recognition of the structures of entrance information, in which the human visual function is unobviously designed are described in the paper. Such methods are called heuristic. They allow reproducing the rules of choice of human optimal decision in the manual mode. The use of these methods is shown on the example of tasks from recognition of speech signals, planning of printed-circuit, task of clusterization and method of structural-alphabetic search.